ROS-related redox regulation and signaling in plants. (August 2018) - Noctor, Graham; Reichheld, Jean-Philippe; Foyer, Christine H.
Abstract: As sessile oxygenic organisms with a plastic developmental programme, plants are uniquely positioned to exploit reactive oxygen species (ROS) as powerful signals. Plants harbor numerous ROS-generating pathways, and these oxidants and related redox-active compounds have become tightly embedded into plant function and development during the course of evolution. One dominant view of ROS-removing systems sees them as beneficial antioxidants battling to keep damaging ROS below dangerous levels. However, it is now established that ROS are a necessary part of subcellular and intercellular communication in plants and that some of their signaling functions require ROS-metabolizing systems. For these reasons, it is suggested that "ROS processing systems" would be a more accurate term than "antioxidative systems" to describe cellular components that are most likely to interact with ROS and, in doing so, transmit oxidative signals. Within this framework, our update provides an overview of the complexity and compartmentation of ROS production and removal. We place particular emphasis on the importance of ROS-interacting systems such as the complex cellular thiol network in the redox regulation of phytohormone signaling pathways that are crucial for plant development and defense against external threats.